Symptoms and Clinical Manifestations in Perimenopausal and Postmenopausal Women in Asia: A Systematic Review and Meta-Analysis - Rara Arisya Cahyaningtyas; Kayla Faradita Aisyah; Vina Kamila HS; Rifdi Gadiantwan Pratisto; Deska Pradita Herdawati (Asian Journal of Health Research, 2025)
Introduction: Menopause is a physiological transition marked by the permanent cessation of menstruation due to declining ovarian function and estrogen production. The menopausal transition, particularly the perimenopausal phase, is frequently accompanied by symptoms that adversely affect women’s daily functioning and quality of life. This meta-analysis aimed to estimate the relative risk (odds ratio [OR]) of somatic, psychological, and urogenital symptoms among perimenopausal compared with postmenopausal women in Asia.   Material and Methods: A systematic review was conducted following PRISMA guidelines, including studies published within the last 10 years. A total of 14,331 participants were analyzed. Quantitative synthesis was performed using RevMan Cochrane version 5.4.1, with subgroup analysis focusing on hot flushes. Risk of bias assessment indicated moderate to high bias across most included studies.    Results: Perimenopausal women had a significantly higher risk of somatic symptoms than postmenopausal women (OR 1.24; 95% CI 1.20–1.29), particularly hot flushes, night sweats, sleep disturbances, and musculoskeletal pain. Psychological symptoms were also more prevalent during perimenopause (OR 1.05; 95% CI 1.01–1.10), notably anxiety and memory impairment. Urogenital symptoms showed the greatest increase (OR 1.31; 95% CI 1.23–1.40), with vaginal dryness being the most prominent complaint (OR 1.77; 95% CI 1.58–1.98).    Conclusion: Perimenopausal women are at greater risk of experiencing somatic, psychological, and urogenital symptoms than postmenopausal women, with vaginal dryness, sleep disturbances, and cognitive complaints being most pronounced. These findings underscore the impact of hormonal fluctuations during the menopausal transition and highlight the need for early identification and targeted management of menopausal symptoms.